Towards sustainable wastewater treatment: Cost and efficiency trade-offs in the photo-fenton process - Alec Nowell A. Ranara; Redeil N. Arreza; Trisha Kerstin C. Tan; Kathleen B. Aviso; Angelo Earvin Sy Choi (Results in Engineering)
This study examines the efficiency of COD removal in the photo-Fenton process, considering UVA irradiation, Fe2+ concentration, and H2O2 dosage as key operating variables. The primary objective is to simultaneously maximize COD removal and minimize operating costs using fuzzy optimization within a multi-objective framework. Pareto-optimal solutions established COD removal efficiencies ranging from 10.54±1.81 % to 76.58±0.14 %, corresponding to costs of 147.02 to 2087.66 USD·m−3. Fuzzy optimization achieved a 71.12 % overall satisfaction level, balancing trade-offs between performance and cost. Optimal conditions were determined as 83.68 W·m−3 UVA irradiation, 0.4730 mM Fe2+, and 9.00 mM H2O2, yielding a 57.22±0.91 % COD removal at a total cost of 707.40 USD·m−3. This demonstrates a 2.48 times greater cost-efficiency than conventional methods, despite an 18.58 % lower removal efficiency. To improve the photo-Fenton process for industrial applications, future work can consider dynamic optimization for variable wastewater compositions, low-cost catalysts to reduce reagent expenses, hybrid systems to enhance scalability, and real-time monitoring to automate adjustments in irradiation and dosing.